2005
DOI: 10.1590/s1516-635x2005000100003
|View full text |Cite
|
Sign up to set email alerts
|

Economic traits and performance of Italian quails reared at different cage stocking densities

Abstract: This study assessed the effect of different cage stocking densities on the performance of Italian quails in the laying period. Two hundred and sixty four quails with 30 weeks of age and 280g mean body weight were used. Birds were randomly assigned to 96 x 33 x 16 cm cages and distributed in a randomized block design with 4 treatments (12, 15, 18 and 21 quails per cage or 264, 211, 176 and 151 cm² per quail, respectively) and 4 replicates. Birds were given feed and water ad libitum and submitted to the same exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 3 publications
5
29
3
1
Order By: Relevance
“…Similar to the performance results in the present study, HSD was shown to cause decreased FI, FCR, and BW gain, resulting in deteriorated poultry growth performance and welfare (11,12). When the number of birds per unit of space increases, microclimate conditions around the birds deteriorate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to the performance results in the present study, HSD was shown to cause decreased FI, FCR, and BW gain, resulting in deteriorated poultry growth performance and welfare (11,12). When the number of birds per unit of space increases, microclimate conditions around the birds deteriorate.…”
Section: Discussionsupporting
confidence: 81%
“…Quail is a good alternative animal protein due to its low housing, space, and feed requirements as well as diminished waste and higher productivity. Cage density is an important environmental factor affecting production levels and quality in quail meat (11). The goal of quail producers is to achieve a balance between production efficiency and bird welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed quails have smaller body weight and space requirements are small. In addition to, less waste is produced as compared with other conventional livestock projects, and thus it is not so detrimental to the environment (Faitarone et al, 2005). Laying hens todays are primarily housed in battery cages (also called conventional cages).…”
Section: Introductionmentioning
confidence: 99%
“…Such practice is very common and can be seen as aggressive but generally did not interfere in the production system (Leandro et al 2005). The maximization of the production system has brought some issues about the birds welfare (Faitarone et al 2005), once the area per bird is reduced, as well as the feeding area and the water area, causing increase on the stress and at the end, in the final production, as eggs or meat (Carey et al 1995), interfering on the feed consumption and its performance (Pavan et al 2005).…”
Section: Introductionmentioning
confidence: 99%